Pretty girls : a novel - Slaughter, Karin, 1971- (William Morrow, an imprint of HarperCollinsPublishers, 2015)
"More than twenty years ago, Claire and Lydia's teenaged sister Julia vanished without a trace. The two women have not spoken since, and now their lives could not be more different. Claire is the glamorous trophy wife of an Atlanta millionaire. Lydia, a single mother, dates an ex-con and struggles to make ends meet. But neither has recovered from the horror and heartbreak of their shared loss--a devastating wound that's cruelly ripped open when Claire's husband is killed. The disappearance of a teenage girl and the murder of a middle-aged man, almost a quarter-century apart: what could connect them? Forming a wary truce, the surviving sisters look to the past to find the truth, unearthing the secrets that destroyed their family all those years ago . . . and uncovering the possibility of redemption, and revenge, where they least expect it" --